2010
DOI: 10.3201/eid1609.100076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pandemic (H1N1) 2009 and Seasonal Influenza, Western Australia, 2009

Abstract: TOC summary: Infections were similar in terms of symptoms, risk factors, and proportion of patients hospitalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 22 publications
8
30
2
Order By: Relevance
“…This results is contrary to previous reports on hospitalized patients (25,27,(37)(38)(39), which showed that A(H1N1)pdm09 infection was associated with a higher percentage of severe cases and mortality. However, reports from Australia (40), Hong Kong (41), and Japan (32) were consistent with our study. The reason for the difference between different studies may be mainly due to the subjects included in the studies.…”
Section: Discussionsupporting
confidence: 93%
“…This results is contrary to previous reports on hospitalized patients (25,27,(37)(38)(39), which showed that A(H1N1)pdm09 infection was associated with a higher percentage of severe cases and mortality. However, reports from Australia (40), Hong Kong (41), and Japan (32) were consistent with our study. The reason for the difference between different studies may be mainly due to the subjects included in the studies.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that the rate of positive influenza virus was the same as the range described in Malaysia, Taiwan, and Western Australia studies (2,11,13).…”
Section: Discussionsupporting
confidence: 88%
“…Compared to infections with circulating seasonal influenza A and B virus strains, infection with A(H1N1)pdm09 virus was associated with more severe disease in some human studies (19) but with comparable disease in others (20,21). Comparisons of disease severities and immune responses induced by infection with A(H1N1)pdm09 virus and seasonal influenza A virus strains are limited in animal models (14,22,23), with no studies focusing on coexistent influenza A and B virus strains.…”
mentioning
confidence: 99%